2022
DOI: 10.15537/smj.2022.43.8.20220258
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antioxidant potential of Gardenia latifolia in type-2 diabetic rats fed with high-fat diet plus low-dose streptozotocin

Abstract: Objectives: To test the antidiabetic potential of Gardenia latifolia extract (GLE) in rats with type 2 diabetes mellitus (T2DM) induced by a high-fat diet (HFD) + streptozotocin (STZ). Methods:The study was carried out in June 2021. Gardenia latifolia powdered leaves were subjected Original Articleto Soxhlet extraction using ethanol. Male rats were administered a low dose-40 mg/kg STZ by intraperitoneal route following 2 weeks of HFD to induce type-2 diabetic rats (T2DR). Rats were randomized into 5 groups (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In recent years, gardenia was found to have many pharmacological benefits, such as anti-inflammatory effects, tumor prevention, cardiovascular disease prevention, and water-soluble nutrients that can be easily absorbed in the body [ 15 , 16 , 17 ]. One study showed that the gardenia latifolia extract (GLE) had an anti-diabetic potential in rats with a high-fat diet (HFD) + streptozotocin (STZ) induced type 2 diabetes mellitus (T2DM) [ 18 ]. However, there was less information about the functional mechanism of the hypoglycemic effects of crocin I, geniposide, from gardenia on T2DM in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, gardenia was found to have many pharmacological benefits, such as anti-inflammatory effects, tumor prevention, cardiovascular disease prevention, and water-soluble nutrients that can be easily absorbed in the body [ 15 , 16 , 17 ]. One study showed that the gardenia latifolia extract (GLE) had an anti-diabetic potential in rats with a high-fat diet (HFD) + streptozotocin (STZ) induced type 2 diabetes mellitus (T2DM) [ 18 ]. However, there was less information about the functional mechanism of the hypoglycemic effects of crocin I, geniposide, from gardenia on T2DM in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…This disordered energy can, seemingly quite randomly, damage our cells, and result in oxidative-stress-related diseases such as cardiovascular disease, arthritis, cancer, atherosclerosis, aging, and neurological and neurodegenerative disorders [ 3 , 4 ]. In a healthy body, the oxidizing and reducing forces are—to a large extent—balanced and generate a reasonably controlled energy flow in which the accumulation of oxidative damage is kept within limits, and we can enjoy a lifespan of, on average, 80 years [ 5 ]. Intriguingly, the disordered energy also has a ‘good’ side, as it is involved in cell signaling, e.g., it can lead to adaptation of cells, making them more resilient [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…enjoy a lifespan of, on average, 80 years [5]. Intriguingly, the disordered energy also has a 'good' side, as it is involved in cell signaling, e.g., it can lead to adaptation of cells, making them more resilient [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that complications may develop in some patients despite being under medical control. Therefore, alternative appropriate treatment methods should be developed to treat the disease and prevent complications [2]. Oxidative stress has been noted in the pathogenesis of diabetes, since some complications cannot be prevented despite treatment with insulin or antihyperglycemic drugs.…”
Section: Introductionmentioning
confidence: 99%